Youth, Religious Identity, and Autobiography at the English Colleges in Rome and Valladolid, 1592–1685 - Underwood, Lucy (The historical journal, 2012)
This article analyses the records of 595 entrants to the English College, Rome, and 309 entrants to the English College, Valladolid. These Colleges, set up to train young English men as Catholic priests at a time when Catholicism was proscribed in England, required all entrants to complete questionnaires covering their social, educational, and religious background. The Responsa Scholarum are the autograph manuscripts of students at Rome; the Liber Primi Examinis consists of summaries of oral examinations written down by the interviewers. Through a combination of quantitative analysis and close reading of individual accounts, this article explores responses to the questionnaires, focusing on the engagement of young people with religion and religious identity. It argues that their self-writings shed important light on our understanding of both early modern religion and of early modern childhood and adolescence.